Cellular Mediators of Inflammation: Tregs and TH17 Cells in Gastrointestinal Diseases. (8th February 2010) - Pandolfi, Franco; Cianci, Rossella; Pagliari, Danilo; Landolfi, Raffaele; Cammarota, Giovanni
Abstract : Human lymphocyte subpopulations were originally classified as T- and B-cells in the 70s. Later, with the development of monoclonal antibodies, it became possible to recognize, within the T-cells, functional populations: CD4 + and CD8 + . These populations were usually referred to as "helper" and "suppressor" cells, respectively. However several investigations within the CD8 cells failed to detect a true suppressor activity. Therefore the term suppressor was neglected because it generated confusion. Much later, true suppressor activity was recognized in a subpopulation of CD4 cells characterized by high levels of CD25. The novel population is usually referred to as T regulatory cells (Tregs) and it is characterized by the expression of FoxP3. The heterogeneity of CD4 cells was further expanded by the recent description of a novel subpopulation characterized by production of IL-17. These cells are generally referred to as T H 17 . They contribute to regulate the overall immune response together with other cytokine-producing populations. Treg and T H 17 cells are related because they could derive from a common progenitor, depending on the presence of certain cytokines. The purpose of this review is to summarize recent findings of the role of these novel populations in the field of human gastroenterological disease.